The Effect of PSE and Non-PSE Adductor and Semimembranosus Pig Muscles on the Occurrence of Destructured Zones in Cooked Hams - Martina Eliášová; Josef Kameník; Alena Saláková; Zdeněk Pavlík; Matej Pospiech; Bohuslava Tremlová (Journal of Food Quality)
The aim of this study was to analyse pig muscles used in the production of cooked hams with a view to the occurrence of PSE-type defects and their potential effect on the frequency of destructured zones in finished products. One hundred and six samples of m. adductor (AD) and m. semimembranosus (SM) pig muscles were studied. The two kinds of muscle differed from each other in terms of their pH values and colour (L⁎: lightness, a⁎: redness, and b⁎: yellowness); these differences between the two categories were statistically significant (P<0.001). The AD muscles were divided into meat with PSE (pale, soft, and exudative) defects and non-PSE meat by sensory examination. A total of 44.3% of AD muscles showed PSE defects. Lightness L⁎ fell within a range of 50.68–55.23 in non-PSE meat (AD) and was statistically significantly lower (P<0.001) than in PSE meat (56.25–58.78). Drip loss (AD) was higher (P<0.001) in PSE meat (4.83–6.27%) than in non-PSE meat (3.53–5.0%). Cooked hams prepared from pig muscles showed evident destructured zones when sliced, the number and overall area of which were not affected by the occurrence of PSE defects in the raw meat used.